Strategi Guru PPKn dalam Pelaksanaan Pembelajaran Jarak Jauh Selama Masa Pandemi Covid-19 di Pali, Sumatera Selatan : - - Mariyani, Mariyani; Alfansyur, Andarusni (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2021)
ABSTRACT: A big challenge for Indonesia's education world since the current Covid-19 outbreak. Especially with the existence of a learning from home circular by Kemendikbud in the emergency situation of the Covid-19 pandemic. To overcome the current condition, face-to-face learning becomes learning from home using the internet network. The main problem is when internet-based home learning cannot reach various locations in Indonesia so the learning process does not run optimally. Therefore, the role of the teacher to determine the strategy in implementing distance learning is needed. This study aims to determine the strategies of civic education teachers in implementing distance learning during the Covid-19 Pandemic at PALI, South Sumatra. The research method used is descriptive qualitative with 4 civic education teachers selected according to the research objectives (purposive sampling). The results obtained were that 1) the planning strategy carried out by the civic education teacher was to design learning according to the conditions of students in the area, then socializing online learning through the school website, contacting parents and even socializing to students about online learning; 2) the tactical strategy used by civic education teachers is to make it easier for students to carry out learning with various learning media that can be accessed by all students such as Whats App or Google Classroom; 3) the pattern strategy carried out by civic education teachers is to process learning by utilizing effective learning media and approaches even though there are many obstacles faced by students and teachers. The conclusion of the research is that of the three strategies that civic education teachers do in various conditions, the teacher's planning strategy and tactics have maximized the ability to process online-based distance learning. However, in the pattern strategy to be able to carry out online-based distance learning there are obstacles and challenges given the various economic, geographic, social conditions and even technological affordability in supporting online-based distance learning at PALI, South Sumatra. Keyword: PPKn teacher strategy, Distance learning, Covid-19 Pandemic